Rare earth elements stratigraphic significance in late Permian coal measure from Bijie City, Guizhou Province, China - 王强 杨瑞东 鲍淼 (Journal of rare earths, 2008)
Rare earth elements （REEs） are good geological indicators. In order to understand REEs stratigraphic significance, REEs in Late Permian coal measure from Bijie City, western Guizhou Province, China were studied. The results showed that the contents of both light rare earth element （LREE） and ∑ REE were sharply increased in the boundary between Longtan Formation and Changxing Formation, which resulted from the gyration and discontinuity eruption of Emeishan basalt （REEs source） and frequent transgression-regression during forming coal. The coal measure and strata could be subdivided and correlate, and the sea-level change could be under stood by studying REEs content variation in coal measure.